Efficacies of cooking and depuration for reducing current-use pesticide residues in wild-caught giant mud crabs (Scylla serrata) - Gray, Benjamin C. T.; Champion, Curtis; Broadhurst, Matt K.; Coleman, Melinda A.; Benkendorff, Kirsten (Frontiers in Marine Science, 2025)
IntroductionPesticides can be transported into estuaries via spray drift, ground water contamination and surface runoff. Increasing climatic variability and global pesticide use are likely to increase the exposure of harvested estuarine species, and therefore seafood consumers, to agrichemicals. Post-harvest processing strategies present opportunities to reduce pesticide residues in seafood and so mitigate consumer exposure.Materials and methodsWe evaluated the efficacies of thermal processing (cooking) and depuration (holding individuals in clean flow-through seawater) for reducing pesticide residues in wild-caught giant mud crab (Scylla serrata) edible tissues (flesh and brown meat (i.e. hepatopancreas and gonads)). Pesticide residues were detected in 82% of assessed crabs, with five analytes quantified (cyprodinil, diuron, imidacloprid, propargite and triazophos).ResultsCorrelative analyses revealed cooking at 82°C for 2 min 100-g–1 body mass reduced all pesticide concentrations (and the total residues) in both tissues by 7–99%—except for cyprodinil (51% increase). Imidacloprid residues in crab flesh were reduced (by 81%) after six days of depuration, with complete elimination after 12 days. While a human health-risk assessment identified that the concentrations of pesticide residues in crab tissues posed no negative health effects to seafood consumers, the data support post-harvest processing methods for mitigating consumer exposure.DiscussionThese findings do not constitute health advice regarding post-harvest possessing methods for reducing contaminants in seafood, but rather highlight the potential utility of the methods assessed for achieving this objective and the broader need for ongoing pesticide surveillance of Australian seafood. Food safety regulation should consider establishing maximum residue limits for seafood, with consideration of consumption preferences.